In vitro genotoxicity of dibutyl phthalate on A549 lung cells at air–liquid interface in exposure concentrations relevant at workplaces. (19th October 2021) - Binder, Stephanie; Cao, Xin; Bauer, Stefanie; Rastak, Narges; Kuhn, Evelyn; Dragan, George C.; Monsé, Christian; Ferron, George; Breuer, Dietmar; Oeder, Sebastian; Karg, Erwin; Sklorz, Martin; et al.
Abstract: The ubiquitous use of phthalates in various materials and the knowledge about their potential adverse effects is of great concern for human health. Several studies have uncovered their role in carcinogenic events and suggest various phthalate‐associated adverse health effects that include pulmonary diseases. However, only limited information on pulmonary toxicity is available considering inhalation of phthalates as the route of exposure. While in vitro studies are often based on submerged exposures, this study aimed to expose A549 alveolar epithelial cells at the air–liquid interface (ALI) to unravel the genotoxic and oxidative stress‐inducing potential of dibutyl phthalate (DBP) with concentrations relevant at occupational settings. Within this scope, a computer modeling approach calculating alveolar deposition of DBP particles in the human lung was used to define in vitro ALI exposure conditions comparable to potential occupational DBP exposures. The deposited mass of DBP ranged from 0.03 to 20 ng/cm 2, which was comparable to results of a human lung particle deposition model using an 8 h workplace threshold limit value of 580 μg/m 3 proposed by the Scientific Committee on Occupational Exposure Limits for the European Union. Comet and Micronucleus assay revealed that DBP induced genotoxicity at DNA and chromosome level in sub‐cytotoxic conditions. Since genomic instability was accompanied by increased generation of the lipid peroxidation marker malondialdehyde, oxidative stress might play an important role in phthalate‐induced genotoxicity. The results highlight the importance of adapting in vitro studies to exposure scenarios relevant at occupational settings and reconsidering occupational exposure limits for DBP.